How to study effectively. Issue 6 (July 2017) - Fowler, Alexander; Whitehurst, Katharine; Al Omran, Yasser; Rajmohan, Shivanchan; Udeaja, Yagazie; Koshy, Kiron; Gundogan, Buket
Abstract : The ability to study effectively is an essential part of completing a medical degree. To cope with the vast amount of information and skills needed to be acquired, it is necessary develop effective study techniques. In this article we outline the various methods students can use to excel in upcoming examinations.